2013
DOI: 10.3324/haematol.2012.066217
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma thrombopoietin levels in patients with myelodysplastic syndrome: a reliable marker for a benign subset of bone marrow failure

Abstract: ARTICLES 901 Myelodysplastic SyndromesAlthough myelodysplastic syndromes are heterogeneous disorders comprising a benign subset of bone marrow failure similar to aplastic anemia, no laboratory test has been established to distinguish it from bone marrow failures that can evolve into acute myeloid leukemia. Plasma thrombopoietin levels were measured in 120 patients who had myelodysplastic syndrome with thrombocytopenia (< 100 x 10 9 /L) to determine any correlation to markers associated with immune pathophysiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Previous studies on adults reported higher levels of TPO in patients with AA than in patients with MDS . Additionally, our study revealed higher levels of TPO in patients with AA than in patients with hypocellular RCC.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Previous studies on adults reported higher levels of TPO in patients with AA than in patients with MDS . Additionally, our study revealed higher levels of TPO in patients with AA than in patients with hypocellular RCC.…”
Section: Discussionsupporting
confidence: 72%
“…TPO has been identified as a hematopoietic growth factor that regulates the production of megakaryocytes and platelets . High TPO levels have been observed in patients with AA, and these abnormal levels correlate with disease severity …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult to determine the cellularity of megakaryocytes in patients with BM failure, as a BM biopsy specimen taken from an iliac bone site does not accurately represent the number of megakaryocytes in the BM of whole body. We hypothesized that plasma TPO levels may serve as a surrogate marker for the number of megakaryocytes [11], and measured TPO levels in a large number of patients with thrombocytopenia [12]. Similar to the findings from previous studies [13,14], TPO levels in patients with AA were noticeably higher than those in patients with ITP or refractory anemia with excess of blasts (RAEB).…”
Section: Reasons For the Choice Of Ist For Casementioning
confidence: 63%
“…Consistent with the mean baseline serum TPO level of 0.77±0.62 ng/mL reported by Wolff et al [30], we found a value of 553.9±518.1 pg/mL before transplantation. The adverse events were defined using the Common Terminology Using the same assay as that used in our study, Seiki et al [31] showed that the plasma TPO level of healthy individuals was 54.5±21.1 pg/mL, which was significantly lower than that of transplant patients. Therefore, high TPO levels before transplantation might be a compensatory reaction.…”
Section: Discussionmentioning
confidence: 99%